Characteristics of social media influencers and their effect on the purchase intent of consumers in Leyte - Caysido, Danica P.; Cinco, Derville Paz L.; Malquisto, Jhenette R.; Dacuyan, Flordeliz B. (Tacloban City Division of Management, University of the Philippines Visayas Tacloban College, 2022)
The rise of social media influencers became a global phenomenon especially during the lockdowns brought by the COVID-19 pandemic. Business-wise, social media and its social media influencers (SMIs) fostered the connection between businesses and their customers through various social media platforms. The characteristics of influencers who promote brands and their contents can capture the purchasing interest of consumers. However, despite the booming popularity of having SMIs to promote products to customers and to boost sales, there is still skepticism as to whether or not they are indeed effective in convincing customers to make purchases or at least induce them to make one. In this sense, this study aims to determine how the credibility of SMIs is perceived by consumers: the extent to which these influencers' characteristics might affect purchase intention as a general measure of their effectiveness, and if there are differences on the effect of perceived source credibility and popularity based on the sex and age group of the respondents. The study utilized a quantitative research design, in which a survey was conducted with 196 valid responses were collected. Scale that was previously developed by Ohanian (1991) were applied and adapted. Pearson Coefficient Correlation, Multiple Regression Analysis, Independent Sample T-test and Analysis of Variance were used to interpret data. The results revealed that the "physical attractiveness" of an influencer has the strongest relationship with the purchase intent of consumers, which indicates that it is the dimension of source credibility that best explains the consumers' buying behavior. All characteristics considered in this study was found to be significant and can predict the purchase intent of consumers, ranked according to strength from strongest to weakest: physical attractiveness, popularity, trustworthiness and expertise. When analyzed based on sex and age group differences, results revealed that the characteristics "trustworthiness" and "expertise" are significant compared to the other characteristics considered in this study. Male respondents are influenced more by perceived trustworthiness and perceived expertise of influencer more than females. Findings also exhibited that people belonging to the 25 and above age group are cautious consumers, favoring trustworthiness and expertise of the influencer compared to the younger people.
Undergraduate thesis (B.S. in Accountancy) -- University of the Philippines, Tacloban.
Keywords: Influencers (Marketing) -- Philippines -- Leyte